Antibacterial Activities of Ethyl Acetic Fraction of Robusta Coffee on Staphylococcus aureus and Salmonella typhi - Dwi Puji Rahayu (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2020)
Infectious diseases are still a major problem in the world, especially in developing countries like Indonesia. Staphylococcus aureus and Salmonella typhi are gram-positive and gram-negative bacteria that are still the most common cause of infection. Improper use of antibiotics can damage normal flora and cause resistance. Coffee contains flavonoid and alkaloid chemical compounds that have antibacterial activity. The purpose of this study was to determine the antibacterial activity of the ethyl acetate fraction from ethanol extract of robusta coffee beans on the growth of Salmonella typhi and Staphylococcus aureus bacteria. The extraction method used was maceration with 70% ethanol solvent and fractionation using the liquid-liquid method using ethyl acetate solvent. Antibacterial testing uses the disk diffusion method with concentrations of 2.5%, 5%, 10% and 15%. The results of the ethyl acetate fraction with a concentration of 15% for Salmonella typhi bacteria had an inhibition zone of 8.13 mm and Staphylococcus aureus bacteria had a inhibition zone of 3.8 mm. The greater the concentration of ethyl acetate fraction the greater the inhibition zone formed on agar media.